STUDI KASUS PENGGUNAAN MAXIMUM INTENSITY PROJECTION DALAM MENINGKATKAN KUALITAS CITRA PADA PEMERIKSAAN CT UROGRAFI DENGAN KLINIS NEFROLITIASIS - Zahra Sekar Ashsheibyra,; Ildsa Maulidya Mar'athus Nasokha,; Ike Ade Nur Liscyaningsih, (Journal of Innovation Research and Knowledge, 2025)
Background: In CT Urography examinations with clinical nephrolithiasis, small stones are often difficult to detect using standard reconstruction because they are hidden between imaging slices. Maximum Intensity Projection (MIP) is a reconstruction algorithm that displays voxels with the highest attenuation into a two-dimensional image, so that high-density structures such as calcifications appear more clearly. Based on observations at the Radiology Installation of RS X, image reconstruction was added with MIP. This study aims to determine the CT Urography examination procedure and the reasons for using MIP to improve image quality in nephrolithiasis cases. Method: This qualitative research applied a case study approach. The study was conducted at the Radiology Unit of RS X in May 2025. Subjects included three radiographers and one radiologist, as well as CT urography subjects with clinical nephrolithiasis. Data were obtained through observation, documentation, and interviews, then analyzed through data reduction, data presentation, and conclusion drawing. Results: The CT urography examination procedure followed a plain abdominal protocol, with patient preparation including the consumption of 700-1000 mL of warm tea without fasting. Image reconstruction was performed by adding MIP to coronal sections showing abnormalities. MIP provided clearer and more intact visualization of the kidneys with well-defined borders. Kidney stones appeared brighter and had better contrast, with Hounsfield Unit (HU) values ​​at 5 mm slice thickness increasing from 507 to 516 after MIP application. This increase illustrates the mechanism of MIP in displaying voxels with the highest attenuation, making stones easier to recognize. HU values ​​before and after MIP fell within the classification range of calcium oxalate and calcium phosphate commonly found in the urinary tract. Conclusion: The use of MIP has been shown to improve image quality, particularly in visualizing kidney stones, thus supporting diagnostic accuracy and interpretive efficiency. Fasting preparation is still recommended to minimize fecal material and provide clearer visualization of the urinary tract and abnormalities